Chickenpox at Ninety Four:A Case for Extending the Use of Varicella Vaccine in the UK. (16th May 2010) - Bendig, Justin; Sindall, Fiona
Abstract : A case of chickenpox in a 94-year-old female is described. Serological tests for Varicella zoster virus (VZV) performed on early and late serum samples confirmed primary VZV infection. The patient recovered but seventeen days after presentation she developed a stroke from which she subsequently died. Chickenpox in older people is relatively rare—this case may be the oldest case of laboratory-proven chickenpox described—but it is a life-threatening illness. The varicella vaccine is licensed for use in immunocompetent persons of 12 months of age or older but in the UK is only offered to susceptible healthcare workers and close contacts of immunocompromised patients. In the US, the vaccine is recommended for all susceptible adolescents and adults. The same recommendation should be made in the UK.